Mathematical models of stationary chemical-technological processes with random time of process - P. V. Ermuratskiy; Yu. B. Minkin (Тонкие химические технологии, 2010)
In the article a number of chemical and physical processes with random stay time of of particles in the device are considered. On the basis of initial density of distribution of the value of the defining parameter in the particles entering in the device and of density of distribution of time of stay of particles in the device with the use of the kinetic equation of the process proceeding in the device densities of distribution of the defining parameter at the device outlet were obtained. For a cascade of devices density of distribution of probabilities of times of stay of particles in the device and the defining parameter were obtained.